Adsorptive Removal of Bromophenol Blue Dye from Aqueous Solution using Acid Activated Clay - C. C, Okoye; C. F, Okey-Onyesolu; D. C, Chime; C. C, Achike (International Journal of Scientific Research and Management (IJSRM), 2018)
Sulphuric Acid Activated River Niger (SAARC) adsorbent was prepared and used for the treatment of simulated wastewater. The merits of the chemical activation were evident on the characterization results. The morphology of the clay suggested that it belongs to the kaolinite family. Experiments conducted show the percentage of Bromophenol blue (BB) dye adsorbed on SAARC significantly depends on pH, adsorbent dosage, contact time, temperature and dye concentration. Langmuir model best fitted the experimental data compared to the results obtained for Freundlich, Temkin and Dubnin-Radushkevich isotherm models. The Dubinin-Radushkevich isotherm , E, depicts that the adsorption process is physisorption in nature. The experimental data were better described by the pseudo-second order and the power function kinetics models. The feasibility and spontaneity, exothermic nature and decreased randomness at the solid-solution interface were confirmed by the negative values calculated for Gibb’s free energy (ΔG∘), enthalpy change (ΔH∘) and entropy change (ΔS∘) respectively. The results obtained corroborate the potential suitability of the prepared sulphuric acid activated River Niger Clay (SAARC) as an adsorbent